Where are the women? Female artists in art history (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
The Article: “Where are the women? Female artists in Art History” presents a recent didactic exhibition at Artequin Museum Viña del Mar. Its objective was to introduce children to the work of artists of different periods and to reflect about the presence and absence of female artists in the history of art, highlighting gender equity contents as part of an educational program consisting of tours, modules and didactic museography to motivate the dialogue about gender, roles and stereotypes. The educational program analyzed how the gender stereotypes influence all aspects of our lives.